Solusi Eksak Model Linier Injeksi Insulin Dalam Tubuh - Putri Dianwati, Diajeng Maharani; Pagalay, Usman (Jurnal Riset Mahasiswa Matematika, 2024)
This study the insulin injection model in the body has three parts, namely the number of insulin concentrations in the non-monomeric state , the number of h concentrations in the monomeric state , and the number of concentrations in plasma . This study aims to find the exact solution of the insulin injection model in the body and to find out the amount of insulin concentration injected. So that it can provide an understanding of the mechanism of insulin injection absorption in the body. The steps to find the exact solution of the model can be done by the variable separation method and then finding the integration factor and direct integration until the exact solution of the model is found. The results of this study indicate that the linear model of insulin injection in the body is influenced by the amount of insulin dose injected, then this will result in the absorption of insulin contained in the monomeric, non-monomeric and plasma states. The absorption of insulin concentration is also influenced by the magnitude of the factor on the absorption rate, the transfer rate from the subcutaneous tissue to the peripheral compartment and the rate of elimination from the body